A study on customers’ satisfaction towards service quality at Menara Taming Sari Melaka / Fairus Sabran , Mohd Amnn Abu Hussin and Ros Farrah Ain Johar - Sabran, Fairus; Abu Hussin, Mohd Amnn; Ain Johar, Ros Farrah (Faculty of Hotel and Tourism Management, 2013)
The present research was conducted at Menara Taming Sari Melaka, This research intends to measure customers' satisfaction towards the service quality at Menara Taming Sari Melaka which located in Banda Hilir, Melaka, Malaysia, Service Quality (SERVQUAL) model was used to assess service quality that enables management to better understand the dimensions and how they affect service quality and customers' satisfaction. Successful service providers are able to meet and, whenever possible, exceed consumers' needs and wants in delivering services, due to certain specific characteristics of services such as intangibility, simultaneity, variability and perish ability and to the human element, ~ n particular the 'face-to-face' interaction with the customer. The quantitative and qualitative data taken from 150 respondents were analyzed and interpretations of the relationship made. It was found that service quality elements contribute significantly to customers' satisfaction. The customers' satisfaction towards service quality can give benefits to the Menara Taming Sari Melaka itself. Through the service quality, the tower can improve their service in every service quality dimensions.